The Importance of Platelet-Derived Growth Factors as Markers of Survival and Severity of COVID-19 in Patients Undergoing Monthly Follow-Up - Elżbieta Cecerska-Heryć; Dominika Nieszpór; Natalia Serwin; Ewa Pius Sadowska; Marta Gliźniewicz; Bartłomiej Grygorcewicz; Karol Serwin; Anna Michalczyk; Marta Budkowska; Małgorzata Goszka; Aleksandra Polikowska; Radosław Birger; et al. (Hindawi Limited, 2024)
Platelets are the first to reach the site of tissue damage and secrete substances like platelet growth factors (GFs), which perform many different functions in the human body. Many studies suggest that GFs such as transforming GF (TGF), platelet-derived GF (PDGF), or insulin-like GF-1 (IGF-1) may be markers of survival, disease severity, and post-coronavirus disease (COVID) complications. The study aimed to analyze the concentration of TGF-β, IGF-1, and PDGF-BB in COVID-19 patients compared to the control group (GK). The study group consisted of 50 patients (23 men and 27 women) at the time of COVID-19 detection, 7 days after detection, then 14 and 28 days after detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The GK comprised 48 healthy volunteers (25 women and 23 men). IGF-1, TGF-β, and PDGF-BB concentrations in blood serum by enzyme-linked immunosorbent assay (ELISA) methods. There was a statistically significant relationship between the concentration of IGF-1, TGF-β 1, and PDGF-BB in the study group (I-IV blood draw) and the GK (p<0.001). Statistical analysis showed a significant effect on the survival of COVID-19 patients on IGF-1 (p=0.013), TGF-β (p=0.013), and PGDF-BB (p=0.015) levels. The analysis showed a significant effect of COVID-19 symptom severity on IGF-1 levels (p=0.018), as well as TGF-β (p=0.044) and PDGF-BB (p=0.047). In the future, GF may serve as a predictor of disease severity and the development of new treatments for COVID-19. In later studies, the focus should be on finding the relationship of COVID-19 pathomechanism with all the parameters to understand the processes that occur in the body during SARS-CoV-2 virus infection.